Spatial and temporal movement of the Bearded Vulture using GPS telemetry in the Himalayas of Nepal. (8th December 2019) - Subedi, Tulsi R.; Pérez‐García, Juan M.; Sah, Shahrul A.M.; Gurung, Sandesh; Baral, Hem S.; Poudyal, Laxman P.; Lee, Hansoo; Thomsett, Simon; Virani, Munir Z.; Anadón, José D.
Abstract : This study addresses for the first time the movement patterns of the globally near‐threatened Bearded Vulture Gypaetus barbatus in its most important stronghold, the high‐altitude mountain ranges of Asia. Tracked individuals ( n = 8) in the Annapurna Himalayan range (Nepal) foraged over a vast range of 60 715.9 km 2 and our results indicated age‐class differences in the use of space. Territorial adults showed very small annual home‐ranges (K90 = 150.3 km 2 ), whereas immatures wandered extensively and covered vast ranges of the mountains (K90 = 23 930.8 km 2 ). For adults and immatures, these values are notably larger than the other two studied populations in the world (Pyrenees and South Africa). This suggests that the studied Annapurna population might exhibit lower breeding density than in the Pyrenees or South Africa, possibly due to lower food availability.